The Upper Pleistocene occupation of the Témara Region (Morocco) and new data concerning Middle Palaeolithic subsistence behaviour in North Africa: A taphonomic and zooarchaeological approach to the fauna from El Harhoura 2 and El Mnasra - (:unkn) unknown (My University, 2012)
This work presents a taphonomic and zooarchaeological analysis focused on Pleistocene fauna from the Temara region of Morroco with particular emphasis on the recently excavated sites of El Harhoura 2 and El Mnasra. Particular attention is paid to the Aterian (Middle Palaeolithic, MSA), a techno-complex specific to Upper Pleistocene North Africa and whose behavioural aspects remain poorly documented. This is especially the case for hunting practices, site function and the spatial organization of the territory. This work proposes an interpretative model based on large mammal faunas considered in conjunction with the little regional information that is currently available. The results suggest short occupations involving multiple activities during MIS 5. The example of El Mnasra indicates that Aterian groups consumed ungulates of various sizes (Gazelles, Equidae, Suidae, Bovinae, etc.) with the entire chaîne opératoire related to the butchery of carcasses carried out on-site. In addition to large game, these groups also integrated tortoise and shellfish in their diet. The example of El Harhoura 2 demonstrates carnivores who preyed mainly on gazelle to be the site's main occupants during OIS 3- 4, a period which can be correlated with more rigorous climatic conditions and lower sea levels. Aterian groups probably occupied the rockshelter only during brief stopovers. Despite culture changes evident in the lithic industry and the site being used as a burial ground during the ensuing Iberomaurusian period (Late Upper Palaeolithic/LSA), the accumulators of the fauna at El Harhoura 2 remain carnivores and the proportion of species larger than gazelle increases. On a larger scale, these results highlight similarities in subsistence strategies that can be added to other convergent behavioural features such as the use of pigments and the presence of Nassarius sp. beads. During OIS 5, anatomically modern humans (AMH) exploited coastal areas as well as fairly large
Keywords: African Research